Towards Information-Based Welfare Society - Ostasiewicz, Walenty (W kierunku informacyjnego społeczeństwa dobrobytu, 2009)
The primary goal of this paper is to highlight the main features of a new approach to governance on the basis of the transformation of welfare states into welfare societies. For doing that, there are shortly explained such notions as welfare, well-being welfare state, welfare economics and welfare society. Freely circulated and easily accessible information about the performance of all public institutions is a prerequisite of a welfare society. The paper addresses also some questions of indicators and social reporting related to measurement of well-being.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 66, s. 9-20